How Fintech is Reaching the Poor in Africa and Asia : A Start-Up Perspective - Alexander, Alex J. (International Finance Corporation, Washington, DC, 2018)
This note explores the way traditional banks and financial technology companies, or Fintech’s, interact in Africa and Asia, and their ability to offer innovative digital financial services that grant unbanked individuals access to financial transactions. The Fintech sector is experiencing explosive growth in both continents, but while Asian banks have managed to efficiently integrate with Fintech solutions, African banks have been slower to adapt to this change. Still, the outlook for mobile banking remains positive, and its prevalence will boost the financial industry in both regions.